Analisis Pemilihan Atribut Produk Baru untuk Perilaku Keputusan Pembelian Konsumen pada Produk Biokos Botu-Like Series - Hartiwi Prabowo; Synthia Atas Sari; Idris Gautama (Bina Nusantara University, 2007)
Article was made to answer these several questions which are how is application marketing mix of new product PT Martina Berto, what is new product atribute the most dominate for customer and how is buying decided behavior Biokos BOTU-Like Series. The result of the research show that application of marketing mix of by PT Martina Berto is good, customers are satisfaction that service Biokos BOTU-LIKE Series so they will to buy again and new product attribute the most dominate is price attribute at price level Rp94.500,00.